Contention over contagion: Citizen responses to COVID-19 policies - Resnick, Danielle (International Food Policy Research Institute, 2021)
At the outset of 2021, COVID-19 continues to test the limits of state–society relationships in much of the developing world. On January 7, Senegal’s capital Dakar experienced violent demonstrations opposing a nighttime curfew imposed by the government under a new state of emergency law intended to limit the spread of the coronavirus (Ollivier 2021). A week later, Tunisia implemented a new national lockdown, sparking successive nights of rioting in various cities across the country that prompted intervention by the army. In both cases, grievances over the economic impacts of movement restrictions motivated protesters (Cordall 2021).